2004
DOI: 10.1042/cs20030386
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-induced coronary vasodilatation occurs via a non-genomic mechanism: evidence of a direct calcium antagonism action

Abstract: Testosterone decreases myocardial ischaemia in men with coronary artery disease via a coronary vasodilatory action. However, long-term therapy may increase the risk of prostatic carcinoma via activation of the nuclear AR (androgen receptor). In the present study, we have investigated the mechanism of testosterone-induced vasodilatation using isolated rat coronary arteries and thoracic aortae from control and AR-deficient testicular-feminized mice. Vasodilatation induced by testosterone, T-3-OCMO [testosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…Animal and human studies also suggest direct vasoactive properties. Dose-dependent vasodilatory effects are observed in the presence of androgen receptor (AR) antagonists and in testicular feminised mice (40,41). Alternatively, some of the favourable effects attributed to testosterone may be at least partly due to oestradiol, which is also thought to have beneficial actions.…”
Section: Discussionmentioning
confidence: 97%
“…Animal and human studies also suggest direct vasoactive properties. Dose-dependent vasodilatory effects are observed in the presence of androgen receptor (AR) antagonists and in testicular feminised mice (40,41). Alternatively, some of the favourable effects attributed to testosterone may be at least partly due to oestradiol, which is also thought to have beneficial actions.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results have been reported in different experimental conditions by other groups. [106][107][108] The involvement of potassium channels in testosterone-induced vasodilatation has also been studied by many researchers. [109][110][111] Cairrao et al 112 reported that an AR antagonist, flutamide, and an adenosine triphosphate-sensitive potassium-channel inhibitor, glibenclamide, had no influence on the testosterone relaxant effect, whereas a voltage-sensitive potassium-channel inhibitor, 4-aminopyridine, decreased this effect of testosterone.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 99%
“…Additionally, it has been shown to act as a peripheral vasodilator by affecting intracellular calcium regulation and has the potential to increase cardiac output [24]. Some studies have demonstrated that androgen action is mediated by direct calcium antagonism in the vascular smooth muscle [25]. Testosterone is a powerful antagonist of L-type voltage-operated Ca 2+ channels (LVOCCs).…”
Section: Discussionmentioning
confidence: 99%